Review on information searching behavior: books vs internet / Zahari Mohd Amin, Amzari Abu Bakar and Fadhilnor Rahmad - Mohd Amin, Zahari; Abu Bakar, Amzari; Rahmad, Fadhilnor (Faculty of Information Management, 2010)
Internet and books are regarded as the world's two main sources of information. Students, especially in higher leaning institutions rely on these sources in various learning activities. Internet has becoming popular among them, as they regard it as the most useful source of information. However, the importance of books as a source of information cannot be denied. This paper attempts to discover the information searching behaviour of students with regards to the two sources of information and identify which source being used more than the other. Previous research supports the finding that both sources function in the same manner; in providing the required information. The only difference is the method or skills needed retrieving information from either source. Technology through internet may have invaded the world, but the authentic element of books are still indispensible. That is why internet and books are both relevant in fulfilling information needs of student.